SIMULASI UNBK UNTUK SISWA/SISWI TINGKAT SMA - Caeira, Nazario Martins; Anggraini, Dewi; Lenggu, Max ABR Soleman (STIKOM Uyelindo Kupang, 2020)
Computer Based National Examination (UNBK) is a national examination implementation system using computers as the test media. In its implementation, UNBK is different from the paper-based national examination system or Paper Based Test (PBT) which has been running so far. Over time the process of implementing the UNBK still experiences many obstacles and obstacles experienced by students, especially those who live in remote villages, namely the lack of understanding and lack of use of information technology. They are still confused to use information technology equipment such as computers to deal with UNBK later. Based on a review of the problems that occur the author will create a website as a UNBK simulation media, with the aim to simulate the implementation of the UNBK, so that students understand and are familiar with the process of implementing the UNBK. Waterfall is a classic model that is systematic, sequential in building software